Where are real interest rates heading ? Inflation and growth paradoxes in our Central European region. - Giday, András; Szegő, Szilvia Mária (Public Finance Quarterly, 2024)
The systematic decline of real interest rates and the synchronization of fluctuations are in contradiction to some textbook theorems. We assumed that high inflation in our region could have had the effect of reducing public debt.Attention was paid to the special way of depreciation: a forced growth can “eat” some debt as well. We called for an inflationary regime shift. We used macro financial data, inducing forecasts. Surprising blocking emerged in our region as well: common movement in the up and down cycles. The degree of depreciation effect was surprising, too. We found depreciation is expected to reach 14 % of the sovereign debt in the region in years 2014-2026, that is 7 % of their GDP. While depreciation of debt is minimal in countries using the euro, it is considerable (10-25%) in the others. Global growth pressures have reduced the burden of public debt. As we have shown, the losses have been passed on to the debt financiers, including small and medium-sized enterprises in need of financing, while creating a growth paradox for them by curbing their growth potential.